Effect of Sewage Sludge Addition on the Completion of Aerobic Composting of Thermally Hydrolyzed Kitchen Biogas Residue - Hong-tao Liu (BioResources, 2014)
The composting of thermal-hydrolyzed kitchen biogas residue, either with or without sewage sludge, was compared in this study. The addition of sewage sludge increased and prolonged the temperature to a sufficient level that met the requirements for aerobic composting. Moreover, after mixing the compost materials, oxygen, ammonia, and carbon dioxide levels reverted to those typical of aerobic composting. Finally, increased dewatering, organic matter degradation, and similar mature compost production were observed. Overall, the sewage sludge exhibits a potential synergistic effect to facilitate complete aerobic composting of thermal-hydrolyzed biogas residue.